2016
DOI: 10.5114/wiitm.2016.63988
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of the new intragastric balloon End-Ball for treatment of obesity.

Abstract: IntroductionIntragastric balloons (IGBs) have been successfully used to treat obesity for the last 18 years. These balloons are made of different materials and filled with either air or saline. It seems that balloons filled with saline result in more effective weight loss, but are associated with worse tolerance after implantation. In contrast, balloons filled with air are associated with excellent tolerance, but result in less effective weight loss.AimTo report the early safety and effectiveness results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Buzga et al reported a mean weight loss amount of 14.7 kg with 32.1% EWL in 20 patients in 6 months [ 40 ]. The results were similar to those of conventional balloons with a low incidence rate of complications [ 40 ].…”
Section: End-ballmentioning
confidence: 99%
See 1 more Smart Citation
“…Buzga et al reported a mean weight loss amount of 14.7 kg with 32.1% EWL in 20 patients in 6 months [ 40 ]. The results were similar to those of conventional balloons with a low incidence rate of complications [ 40 ].…”
Section: End-ballmentioning
confidence: 99%
“…Buzga et al reported a mean weight loss amount of 14.7 kg with 32.1% EWL in 20 patients in 6 months [ 40 ]. The results were similar to those of conventional balloons with a low incidence rate of complications [ 40 ]. Keren and Rainis recently reported a mean weight loss amount of 23.5 kg, a mean BMI reduction of 6.4 kg/m 2 , and an EWL of 39.2% in 114 patients who were treated with the End-ball; the significant weight loss continued for 1 year after balloon removal [ 19 ].…”
Section: End-ballmentioning
confidence: 99%
“…The Bioenteric intragastric balloon (BIB), also known as ORBERA, has been most widely used in IGB treatment. BIB is made of silicone, which is thicker than polyethylene, and the balloon volume is thus signi cantly bigger and has a high incidence of complications [32]. Buzga et al [32] reported a mean weight loss of 13.9 kg with an EWL of 37.9% in 20 patients in 6 months after End-ball treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BIB is made of silicone, which is thicker than polyethylene, and the balloon volume is thus signi cantly bigger and has a high incidence of complications [32]. Buzga et al [32] reported a mean weight loss of 13.9 kg with an EWL of 37.9% in 20 patients in 6 months after End-ball treatment. Keren and Rainis [33] reported a mean weight loss of 23.5 kg and 39.2% EWL in 114 subjects who were treated the End-ball; the weight loss signi cantly continued for 1 year after End-ball removal.…”
Section: Discussionmentioning
confidence: 99%
“…Among various approaches to treating obesity, endoscopic methods are used in selected cases, including endoscopically placed intragastric balloons (IGBs). The IGB therapy is used as a bridge to definitive treatment, to facilitate weight loss and optimal patient management prior to bariatric surgery [ 4 , 5 ]. Also, it is used to treat extremely obese patients with multiple comorbidities.…”
Section: Introductionmentioning
confidence: 99%